Practical communication theory - Adamy, David (Electromagnetic waves., 2014)
Practical Communication Theory, 2nd Edition enables the reader to quickly and easily generate the answers to real-world problems encountered in specifying, testing, and fielding any type of systems that involve radio propagation. It deals with free space radio propagation and propagation near the ground and over the ridge lines. As a bonus, this book also includes a special antenna and propagation slide rule, with unique scales, along with detailed explanations, and examples, of how to use it. Now in its second edition, Practical Communication has been updated to include new material on radio propagation near the earth in communication bands, which also explains how to use the slide rule scales for each of the appropriate propagation modes. The section on dynamic range has been expanded and there is additional material on knife-edge diffraction. The appendices have also been updated to include extra propagation formulae and graphs.